2023
DOI: 10.1039/d3ce00695f
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-thin carbon-shell coated Ru/RuO2@C with rich grain boundaries for efficient and durable acidic water oxidation

Qian Chen,
Ruonan Wang,
Lin Liu
et al.

Abstract: Developing an acid-stable oxygen evolution reaction (OER) is essential for efficient water splitting, however, high overpotentials and poor stability severely hinder its development. Herein, we present the synthesis of ultra-thin...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Heterojunctions can not only induce synergy to improve catalytic activity but also effectively improve catalytic stability. In particular, heterojunctions with a core–shell structure can effectively protect the core from oxidation and corrosion. , For example, Qiao’s group reported a core–shell Ru@IrO x electrocatalyst that exhibited redistribution of charge across the heterointerface composed of a Ru core and a partially oxidized Ir shell . The energy-dispersive spectroscopy (EDX) overlap map of Ru and Ir elements (Figure j) in HAADF-STEM mode and line profile across a Ru@IrO x nanocrystal (Figure k) showed that Ru and Ir separate and produce core–shell heterostructures.…”
Section: Strategies To Enhance the Acidic Oer Activity And Stability ...mentioning
confidence: 99%
“…Heterojunctions can not only induce synergy to improve catalytic activity but also effectively improve catalytic stability. In particular, heterojunctions with a core–shell structure can effectively protect the core from oxidation and corrosion. , For example, Qiao’s group reported a core–shell Ru@IrO x electrocatalyst that exhibited redistribution of charge across the heterointerface composed of a Ru core and a partially oxidized Ir shell . The energy-dispersive spectroscopy (EDX) overlap map of Ru and Ir elements (Figure j) in HAADF-STEM mode and line profile across a Ru@IrO x nanocrystal (Figure k) showed that Ru and Ir separate and produce core–shell heterostructures.…”
Section: Strategies To Enhance the Acidic Oer Activity And Stability ...mentioning
confidence: 99%